BENCHMARKING ENVIRONMENTAL PERFORMANCE (ISO 14000 ETC.) OF FIRMS IN THE UK AND LINKING TO OPERATIONS PERFORMANCE (ISO 9000, ETC.) AND FINANCIAL PERFORMANCE - Joshua, Sushmith (2011)
This dissertation involves analysing the financial performance of organizations in the automotive industry in UK that implement ISO standards and comparing their performance with firms that do not implement these standards. Several scholars have previously studied this subject and conflicting results were obtained. In order to contribute towards this growing field of interest, financial data and details of certification were gathered in order to perform the analysis. Financial variables were chosen, which formed the basis for financial performance comparison. The organizations were then segregated into various classifications in order to perform the analysis categorically. Analysis in the form of descriptive statistics and t-tests were then performed on both ISO accredited and non-certified organizations. An in-depth variable-wise analysis was carried out with these analysis techniques, to find the variation of performance between the two groups. The results obtained were biased towards ISO certified firms. This variation in performance was found to be excessively vast in small firms in the automotive industry in UK, whereas there was not much of variation in the medium and large sectors.